Assessing Variuos Interventions Guiding the Effectiveness of Local Economic Development Initiatives for Local Governments of Ohangwena region, Namibia - SHIWAYU, Eliud Mandume; Haufiku, Isdor; Nghuushi, Paulus Ndatiheeno (Papanda Publishier, 2025)
The core objective of this study was to assess various interventions guiding the effective implementation of local economic development (LED) initiatives for local governments (LGs) of the Ohangwena region (OhR) in Namibia and elsewhere worldwide. The Acts, Theories, Economic Policies, and Procedures are designed for sustainable measurements of MDGs in comprehending the SDGs in LGs toward the interlinkages of economic, social, institutional, political, and environmental features. Therefore, the study assessed various theories, acts, policies, and procedures that provide a framework for exploring the processes of effective interventions by LGs in a management sense. A questionnaire and an interview guide were used and designed according to the objectives of this study. The data was collected through mixed-method research (MMR) and analyzed using Microsoft Excel (MSE) for quantitative data, and inductive thematic analysis (ITA) for qualitative data, which provided relevant analysis for the data. The results of the study on Theories 89%, Acts 91,2%, Policies, Procedures, and Regulation 91,3% would effectively bolster LED management through evidence-based interventions guided by internal and external stakeholders to confirm the effective interventions for best practices of LED initiatives toward sustainable measurements and minimal standards of various interventions for effective LED initiatives in LGs. The article assessed the economic policies, procedures, theories, acts, and institutions needed to generate and sustain economic growth and development. It argues that the effectiveness of LED initiatives represents an informative and integrated understanding of interventions on policies, procedures, acts, theories, and institutional reforms needed in broad local areas of LGs.